2017
DOI: 10.1159/000455914
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants of Vitamin D Receptor Gene Polymorphisms and Susceptibility to Coronary Artery Disease: A Systematic Review and Meta-Analysis

Abstract: Background and Aims:ApaI, FokI, TaqI, and BsmI polymorphisms in the vitamin D receptor (VDR) gene have been reported to be associated with the risk of coronary artery disease (CAD), although the results of previous studies have been inconsistent. The aim of this study was to explore whether these polymorphisms play a role in the genetic susceptibility to CAD. Methods: A comprehensive search of Medline and Embase databases was conducted for studies evaluating the association between the VDR polymorphisms and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Another approach is the Mendelian randomization (MR) procedure [5], and there are several single nucleotide polymorphisms (SNPs) related to enzymes needed for activation, transport and breakdown of vitamin D, as well as in the VDR. However, the results have not consistently been in favour of vitamin D. Thus, SNPs related to synthesis and breakdown of 25 Similarly, there have been numerous studies on VDR SNPs, in particular regarding cancer, but also these have shown conflicting results [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is the Mendelian randomization (MR) procedure [5], and there are several single nucleotide polymorphisms (SNPs) related to enzymes needed for activation, transport and breakdown of vitamin D, as well as in the VDR. However, the results have not consistently been in favour of vitamin D. Thus, SNPs related to synthesis and breakdown of 25 Similarly, there have been numerous studies on VDR SNPs, in particular regarding cancer, but also these have shown conflicting results [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐known that VDR is variable across human populations. Several single nucleotide polymorphisms (SNPs) have been described, some of them (e.g., rs1544410, rs731236, rs2228570, and rs7975232, also known as BsmI, TaqI, FokI, and ApaI, respectively) because they are associated with several phenotypes of interest (bone mineral density, protection/susceptibility from ovarian and breast cancer, among others) (Alizadeh, Djafarian, Alizadeh, Mohseni, & Shab‐Bidar, 2017; Nunes et al, 2016; Santoro et al, 2015). Hochberg and Templeton (2010) proposed that VDR alleles belong to the evolutionary complex that adapts humans to UVR to the different exposure levels.…”
Section: Human Skin Color Variation and The Role Of The Vitamin D Undmentioning
confidence: 99%
“…A recent meta-analysis on 5259 cases with risk of coronary artery disease (CAD) and 1981 controls showed that Fok I, Bsm I, Taq I, and Apa I polymorphisms in the VDR might not be associated with CAD [52].…”
Section: Vdrmentioning
confidence: 99%